Practice-Crosscutting Concept pairs of the NGSS and ways of knowing in the Earth & Space Sciences. Issue 2 (3rd April 2023) - Price, Nancy A.
Abstract: The epistemic components of science are included in instruction through the three-dimensional learning of the Next Generation Science Standards (NGSS). Students use the Science & Engineering Practices to engage the Disciplinary Core Ideas through the perspective of the Crosscutting Concepts. The NGSS focus on the epistemic aspects that all sciences share, but the domain-specific epistemic aspects, referred to here as ways of knowing, are still important to include in science education because they require different pedagogical methods. In this paper, I show how curriculum developers can incorporate the ways of knowing of the Earth & Space Sciences into their units through the choice of Practices and Crosscutting Concepts in the lesson-specific learning performance statements. I start by identifying the most common Practice-Crosscutting Concept pairs of the Earth & Space Sciences performance expectations and comparing them to the literature on the ways of knowing in the geosciences. The performance expectations represent the multiple modes of inquiry and systems thinking characteristic of the Earth & Space Sciences. Yet, they don't effectively represent other aspects of the Earth & Space Sciences, like visualization, spatial reasoning, deep time, and large size and spatial scales. I then encourage curriculum developers to move beyond the example of the performance expectations by providing suggested Practice and Crosscutting Concept pairs and groupings that can be used by curriculum developers to communicate these other aspects. I also include example unit outlines to show what the suggestions might look like in application.